LEGAL REVIEW OF THE RIGHTS OF ONLINE MOTORCYCLE JEK DRIVERS TO HOLIDAY BONUSES IN EMPLOYMENT RELATIONS BASED ON CIRCULAR LETTER OF THE MINISTER OF MANPOWER NO. M/3//HK.04.III/2025 - Simamora, Kamaluddin; Sahliah, Sahliah (Journal Analytica Islamica, 2026)
The rapid expansion of application-based transportation has transformed employment relations in Indonesia, particularly in the digital partnership model between platform companies and online motorcycle taxi drivers. Unlike formal workers, online drivers are categorized as partners, thereby excluding them from structural entitlements such as religious holiday allowances (THR) under Minister of Manpower Regulation No. 6 of 2016. In 2025, the government issued Circular Letter of the Minister of Manpower No. M/3/HK.04.00/III/2025 encouraging platform companies to provide a religious holiday bonus equivalent to 20% of drivers’ average annual net income. This study aims to analyze the juridical status of the holiday bonus within Indonesia’s labor law framework and to examine its implementation and fairness in Medan City. Employing a normative-empirical method with a qualitative approach, this research integrates regulatory analysis, doctrinal legal review, and field interviews with online motorcycle taxi drivers. The findings indicate that the partnership status limits drivers’ formal labor rights; however, the ministerial circular represents an initial state intervention toward enhancing protection for workers in the digital informal sector. Empirical data reveal inconsistencies in implementation, lack of transparency, and disparities in bonus distribution, leading to perceptions of distributive injustice. The study contributes to labor law discourse by highlighting the need for clearer regulatory frameworks governing digital platform workers and strengthening legal protection mechanisms in Indonesia’s evolving gig economy.